Antitumor immune response is associated with favorable survival in GEP-NEN G3. Issue 10 (2nd September 2021) - Rosery, Vivian; Reis, Henning; Savvatakis, Konstantinos; Kowall, Bernd; Stuschke, Martin; Paul, Andreas; Dechêne, Alexander; Yang, JiaJin; Zhao, Ben; Borgers, Arianna; Kasper, Stefan; Schuler, Martin; et al.
Abstract : The tumor immune microenvironment (TME) represents a key determinant for responses to cancer treatment. However, the immune phenotype of highly proliferative gastroenteropancreatic neuroendocrine neoplasms (GEP-NEN) is still largely elusive. In this retrospective study, we characterized the TME of high-grade (G3, Ki-67 > 20%) GEP-NEN. We analyzed formalin-fixed paraffin-embedded samples from 37 patients with GEP-NEN G3 by immunohistochemistry and multiplex immunofluorescence to address the abundance and spatial interaction of relevant immune subsets. We focused on the expression of immune checkpoint molecules PD-1 and PD-L1, the cytotoxic T-cell marker CD8, and the tumor-associated macrophage marker CD206. Findings were correlated with overall survival (OS) from the date of a cancer diagnosis. Patients with PD-L1-positive tumors (CPS ≥ 1) and intense PD-1 + CD8 + immune cell infiltration showed the most favorable median OS. Multiplex immunofluorescence staining of ten representative tissue samples illustrated intratumoral heterogeneity of PD-L1 expression. Dense PD-1 + CD8 + immune cell infiltrates were observed in PD-L1-positive tumor regions but not in PD-L1-negative regions. Proximity analysis revealed a spatial interaction between PD-1 + CD8 + cells and PD-L1-positive cells. Our data suggest a pre-existing antitumor immune response in the TME in a subgroup of GEP-NEN G3. This supports a targeted clinical exploration of immunotherapeutic approaches.